ELECTRONIC-STRUCTURE OF THE SULFUR NITRIDES - ABINITIO CALCULATIONS AND PHOTOELECTRON-SPECTRA - Findlay, R; Palmer, M; Downs, A; Egdell, R; Evans, R (1980)
Ab initio molecular orbital calculations of better than double-ζ quality are reported for SN, S2N2,S4N4, and a number of open-shell cationic states; midbond functions (on all molecules) and polarization functions on S2N2 are included. The gas-phase UV-photoelectron spectra (PES) up to 25 eV have been investigated and assigned on the basis of the calculations and cross-section changes under He I/He II irradiation. The electronic structures of S2N2 and S4N4 were investigated by transformation of the wave functions to a localized bond basis. A significant amount of S-S bonding was calculated for S4N4 but no N-N bonding. Across ring bonding was absent from S2N2. © 1980 American Chemical Society.